(untitled) (VITAL, 2025)
On September 19, 2024, the Universidad Juárez Autónoma de Tabasco and the Universidad Antonio Nariño organized a mirror class on breastfeeding with 124 participants, highlighting topics such as its economic and social impact, laws in Mexico and Colombia, and its role in the prevention of obesity. Then, on October 15, 2024, the International Symposium on Breast Pathology: “Hablemos de cáncer” was held virtually.